Pengaruh Corporate Hedging Terhadap Cost Of Debt - Vicki Lineous Suryagari; Fitri Ismiyanti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2017)
The ongoing globalization era is marked by free trade, will bring uncertainty to the Indonesian economy. These uncertainties include fluctuations of exchange rate, interest rates, and commodity prices. This will certainly pose risks, including financial risks that can increase the firm's cost of debt as a risk premium for investors. This study aims to determine the effect of hedging calculated using dummy variable to cost of debt proxies with yield spread. In addition, the bond age, credit rating, leverage, and profitability are used as control variables. The sample which used is manufacturing firm that issues bonds and is listed on the Indonesia Stock Exchange (IDX) for the period 2009-2015. The result of multiple linear regression shows that hedging has a significant negative effect on the cost of debt. Bond age and credit rating have a significant negative effect on cost of debt. Leverage has no significant positive effect on cost of debt. Profitability has no significant negative effect on cost of debt. Hedging lowers cost of debt through decreased bankruptcy costs, agency costs, and information asymmetry. So firms that use hedging will have a lower cost of debt than non-users.